What an election poster can tell us about Thai election campaigns - RICKS, Jacob I. (Institutional Knowledge at Singapore Management University, 2019)
In the runup to Thailand’s 2019 national elections, the country has been awash with election posters. This simple form of campaign communication remains a staple of Thai campaigns, despite the advent of various Internet platforms and communication devices. But although election posters are often discussed by journalists and the general public, they are rarely analyzed in academic research. This is surprising and unfortunate, since their wealth of textual and visual information can tell us a lot about campaigns.